Reconstruction of Restrictions on the President's Power in Determining the Posture of Ministries in the Indonesian Government System - Saifulloh, Putra Perdana Ahmad; Yuliandri, Yuliandri; Simabura, Charles; Fahmi, Khairul; Nur, Asrul Ibrahim (Jambura Law Review, 2025)
This research is a critique of the 2024 State Ministry Law which gives the President the freedom to form Ministries according to his needs.. Based on this law, the President, Prabowo Subianto, formed a Cabinet consisting of 48 Ministries. For this reason, it is urgent to immediately enact a Presidential Agency Law to limit the President's power in determining the posture of ministries so that their functions do not overlap, do not reflect cabinet affairs, and prevent corruption. Through the Presidential Agency Law, it is hoped that the President will not use Ministerial positions as political barter and "share power" with political parties, coalitions and volunteers in General Elections. This research is normative research with statutory, historical, comparative and conceptual approaches. In this study it was concluded: 1).Cabinet dynamics in Indonesia after the enactment of the 2008 Law on State Ministries, namely, the Indonesia Bersatu; The Kerja Cabinet; and The Indonesia Maju Cabinet has Cabinet members, 34 Ministry; and Merah Putih Cabinet,  The number of Cabinet members is 48 Ministries in accordance with the 2024 State Ministry Law which gives the President the freedom to form Ministries according to his needs. 2).Design a Reconstruction of Restrictions on the President's Power in Determining the Posture of Ministries in the Indonesian Government System, namely: First, Establishing the Presidential Agency Law. Second, the Law on Presidential Agency must regulate the maximum number of 24 Ministries. Third, the amalgamation of Institutions within the President's circle to become an integral part of the Ministry of State Secretary. Fourth, the abolition of the Coordinating Ministry Institution. Fifth, Elimination of the Position of Vice Minister